Pathway engineering and metabolic flux analysis of acetyl-coA biosynthesis. - Hee, Kai Sheng. (2011)
Acetyl-CoA is a highly energetic molecule which serves as a precursor for both catabolic and anabolic process in a cell. In this project, we demonstrated the usage of flux balance analysis on the Saccharomyces cerevisiae , iIN800 for Acetyl-CoA biosynthesis for fatty acid pathway using glucose as their carbon source and it is grown under limited oxygen condition. A few metabolic engineering strategies including single and multiple gene deletion are employed in search of the best pathway for Acetyl-CoA biosynthesis. The flux balance analysis method automatically redistribute the pathway after each genetic manipulation in attempt to rebalance the delicate flux rate of the intermediate metabolite species in the in silico model. In this project, the best single gene deletion records the biosynthesis of Acetyl-CoA flux rate 67.3943gDW/hour while generating 8.1977 gDW/hour of fatty acid while multiple gene deletion records a higher flux rate of Acetyl-CoA at 139.975 gDW/hour producing fatty acid at11.2529 gDW/hour.